RAMADAN AS A MOMENTUM FOR CHARACTER DEVELOPMENT: A VALUES EDUCATION APPROACH IN THE ISLAMIC SCHOOL CURRICULUM - Wirawati, Sri Mukti; Abdullah, Aji; Gymnastiar, Iman Ahmad; Rokhim, Abdur; Arthawati, Sri Ndaru (Indonesian Journal of Studies on Humanities, Social Sciences and Education, 2025)
This article examines Ramadan as an essential momentum for character development through a values education approach within the Islamic school curriculum using a systematic literature review. Character development has become increasingly vital, highlighting the importance of embedding moral values and ethical awareness among students. Ramadan presents a unique educational context due to its emphasis on spiritual growth, moral reflection, and behavioral discipline central to Islamic teachings. The systematic review analyzes existing literature sourced from reputable academic databases, focusing explicitly on values-based educational practices conducted during Ramadan in Islamic educational institutions. The findings indicate that Ramadan significantly facilitates the internalization of essential values such as empathy, patience, gratitude, discipline, spirituality, and social responsibility among students. The identified instructional strategies include reflective classroom dialogues, experiential learning activities, and structured community engagement programs integrated into Ramadan-specific curricula. The reviewed literature demonstrates measurable positive impacts on student behaviors, ethical reasoning, interpersonal relationships, and overall character maturity following participation in these curricular practices. Challenges identified in the literature relate mainly to sustaining and consistently applying values education beyond the Ramadan period. This article provides insights and practical implications for educators and policymakers to strengthen character education initiatives within Islamic schooling contexts. Further research is recommended to evaluate the long-term effectiveness of Ramadan-based values education programs and their potential application in broader educational settings.